Effect of pretreatments on the viability of seeds from five Passiflora species - Salazar-Mercado, Seir Antonio; Quintero-Caleño, Jesús David; Palencia-Delgado, Yordan Arley; Salcedo-Garcia, Pedro Isaac (Revista de Ciencias Agrícolas, 2026)
Given the economic importance of Passiflora species in Colombia and the low germination rate caused by their marked dormancy, it is necessary to optimize rapid and accurate quality control protocols that guarantee viable seeds for agriculture. This study evaluated the effect of different pretreatments on the viability of seeds from five species of Passiflora spp. (P. edulis, P. tripartita var. mollissima, P. edulis f. edulis, P. quadrangularis, and P. vitifolia) through the application of tetrazolium (TZ) and indigo carmine (IC) biochemical tests, complemented by a germination assay. Six experimental pretreatments were applied: sodium hypochlorite (NaClO), calcium hypochlorite (Ca(ClO)₂), gibberellic acid (GA₃), potassium nitrate (KNO₃), distilled water, and an untreated control, evaluating two concentrations of TZ and one of IC at three exposure times. The results showed that GA₃, KNO₃, and Ca(ClO)₂ were the most effective pretreatments for increasing the detected viability, with responses above 80% in several species, especially when using TZ at 0.25%. Sodium hypochlorite had the lowest values, even zero in some cases. In general, TZ at 0.25% showed better viability values than 0.1%, while IC showed intermediate values but complemented the evaluation of membrane integrity. The germination test confirmed the trends found in the biochemical assays and showed that in species with pronounced dormancy, physiological viability does not always translate into germination without pretreatment. The results obtained provide technical criteria for optimizing quality control and seed conservation protocols in Passiflora spp., with direct implications for agricultural production and biodiversity preservation.